2007
DOI: 10.3346/jkms.2007.22.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Laparoscopic Splenectomy in Patients with Immune Thrombocytopenic Purpura

Abstract: Laparoscopic splenectomy (LS) has been reserved for intractable and relapsing immune thrombocytopenic purpura (ITP) despite medical treatment. With further experiences of LS in ITP, we investigated long term outcomes of LS, especially newly developed morbidities, and tried to find predictive factors for favorable outcomes. From August 1994 to December 2004, fifty-nine patients whose follow-up period was more than 12 months after LS were investigated. After a long-term follow-up (median 54 months, range 12.5-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…But the overall complication rate is low in LS. [24,30] As our study, Tsereteli et al, [31] did not find any significant difference between the open and laparoscopic procedures as a predictive factor of favorable outcome.…”
Section: Discussionsupporting
confidence: 53%
“…But the overall complication rate is low in LS. [24,30] As our study, Tsereteli et al, [31] did not find any significant difference between the open and laparoscopic procedures as a predictive factor of favorable outcome.…”
Section: Discussionsupporting
confidence: 53%
“…For those who fail to respond to these treatments or who require continued treatment, a splenectomy may be considered (Cines & Bussel, 2005;Nakhoul et al, 2006). Although splenectomy is an effective treatment for many patients, with approximately three-quarters achieving a durable response (Kumar et al, 2002;Kang et al, 2007), it carries with it an increased risk of infection (Kang et al, 2007) and a risk of death from postsplenectomy sepsis of up to 1% (Kumar et al, 2002).…”
Section: Current Management Of Patientsmentioning
confidence: 99%
“…First, it had a longer follow-up period (mean, 84 months) than previous studies: one had a mean of 43.6 months and a range of 9∼114 months 7 ; another had a mean of 20±14 months; 19 and a third had a mean of 54 months and range of 12.5∼129 months. 18 Second, this study demonstrated lower morbidity and mortality rates. In this study, regardless of diagnosis, the overall morbidity rate was 5.8%.…”
mentioning
confidence: 62%
“…Other studies reported an 80.3% long-term response rate of the 127 patients, 7 an 85% rate of remission in the total of 147 patients, 19 and an 88.2% response rate and 15.2% relapse rate during the follow-up period in 59 patients (Table 6). 18 Also, in this study, a single relapsed patient was treated with re-operation by laparoscopic method, so this result must be excellent outcome. Furthermore, compared to previous studies, this study had some strengths.…”
mentioning
confidence: 86%
See 1 more Smart Citation